DETEKSI ANAPLASMOSIS PADA SAPI PERANAKAN FRIESIAN HOLSTEIN (PFH) DI PUSKESWAN KOTA BATU: DETECTION OF ANAPLASMOSIS IN FRIESIAN HOLSTEIN (PFH) CATTLE AT PUSKESWAN AND RPH BATU CITY - Muhammad Masud Chabiburrochman; M Fuad Kurniawan; M Elmanaviean; Izzun Nastiti (Universitas Boyolali, 2026)
Early detection of Anaplasmosis is essential to prevent infection in host cells. Anaplasmosis is transmitted through disease vectors that are usually transmitted by vectors (Karlsen, 2020). The main vector of Anaplasma phagocytophilum is the tick Ixodes ricinus. Anaplasmosis in cattle is generally caused by Anaplasma bovis, Anaplasma marginale, and Anaplasma centrale, which are reported to infect cattle. Confirmation of the diagnosis can be through blood tests and PCR. Appropriate diagnosis and therapy are necessary to prevent the condition of animals infected with blood parasites from worsening. This research data is based on data on Anaplasmosis cases in cattle collected from the health data of PFH cattle in Batu City. The research animals used were beef cattle, namely PFH cattle, with a total of 30 samples. Observations were first carried out in each sub-district, then 10% were taken from each sub-district in Batu City. This study aims to identify blood samples from dairy cattle based on sex, age, and breed of the cattle, namely Friesian Holstein Cross (PFH). Detection of Anaplasmosis in Friesian Holstein Cross (PFH) Cattle at the Animal Health Center and Slaughterhouse in Batu City was obtained. The diagnosis of anaplasmosis in animals was determined based on signals, anamnesis, and physical examination, confirmed by supporting examinations, namely blood smears and blood hematology. Treatment of anaplasmosis cases in Friesian Holstein cattle at the Batu Animal Health Center is with symptomatic therapy in the form of multivitamins (injectamine) and antibiotics (oxytetracycline).